2022
DOI: 10.1186/s40462-022-00310-z
|View full text |Cite
|
Sign up to set email alerts
|

Compensation for wind drift prevails for a shorebird on a long-distance, transoceanic flight

Abstract: Background Conditions encountered en route can dramatically impact the energy that migratory species spend on movement. Migratory birds often manage energetic costs by adjusting their behavior in relation to wind conditions as they fly. Wind-influenced behaviors can offer insight into the relative importance of risk and resistance during migration, but to date, they have only been studied in a limited subset of avian species and flight types. We add to this understanding by examining in-flight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…We used Movebank to filter location quality based on Cyclic Redundancy Check status for Lotek tags. Then, we used the SDLFilter package (Shimada et al, 2012 ) in Program R to remove duplicate points and outliers based on a speed threshold of 150 km/h (Linscott et al, 2022 ; Shimada et al, 2012 ). The SDLFilter package calculates speed based on GPS locations and timestamps and can also detect duplicate points in space and time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used Movebank to filter location quality based on Cyclic Redundancy Check status for Lotek tags. Then, we used the SDLFilter package (Shimada et al, 2012 ) in Program R to remove duplicate points and outliers based on a speed threshold of 150 km/h (Linscott et al, 2022 ; Shimada et al, 2012 ). The SDLFilter package calculates speed based on GPS locations and timestamps and can also detect duplicate points in space and time.…”
Section: Methodsmentioning
confidence: 99%
“…We applied the following criteria to identify stopover sites: (1) ≥3 consecutive points within 30 km of one another or at least 6 h within the area, and (2) not within wintering or breeding areas. We chose to classify both short and long stopping periods as stopovers because birds may stop over for a variety of purposes that may influence their decision‐making and fitness (Linscott & Senner, 2021 ), and our high data resolution allowed us to identify stopover events that would not be detectable with less data. We then visually identified stopover sites and in a few cases where a bird left a stopover site briefly (one point) and later returned we ascribed that area as one stopover site.…”
Section: Methodsmentioning
confidence: 99%
“…Others have noted similar patterns and concluded that these winds would carry migrants south-east out over the Atlantic and down into the eastern trade winds, which would push them back west to South America (Williams et al, 1977;Richardson, 1979;Stoddard et al, 1983). This route could allow shorebirds to maintain a constant heading, relying on tail winds and wind drift with minimal compensation to reach their destination [see Linscott et al (2022) for definitions of responses to wind flow direction]. Work on passerines suggests that migrants that use a time-minimizing strategy may be less selective of wind conditions than those that are energy-minimizers (McCabe et al, 2018).…”
Section: Conditions Affecting Departure Timingmentioning
confidence: 97%
“…2017). This godwit population breeds in Alaska, migrates eastward across North America then southward through interior South America, and terminates on Chiloé Island; northward migration is over the Pacific Ocean, through midcontinent North America then westward to boreal and Arctic Alaska (Senner et al 2014, Linscott et al . 2022).…”
mentioning
confidence: 99%
“…A high proportion (>95%) of the 21,000 Hudsonian Godwits (Limosa haemastica) spending the boreal winter along the Pacific coast of the Americas (Andres et al 2012) use coastal wetlands in the Chiloé Island archipelago (hereafter Chiloé) in southern Chile (Morrison and Ross 1989, Espinosa et al 2005, Andres et al 2009, García-Walther et al 2017. This godwit population breeds in Alaska, migrates eastward across North America then southward through interior South America, and terminates on Chiloé Island; northward migration is over the Pacific Ocean, through midcontinent North America then westward to boreal and Arctic Alaska (Senner et al 2014, Linscott et al 2022.…”
mentioning
confidence: 99%